Vasculitis. Issue 6 (June 2014) - Tweed, Conor
Vasculitis is the umbrella term used to describe a cluster of autoimmune conditions that are characterised by inflammation of the walls of blood vessels. This inflammation can be due to a primary disease or secondary to an existing condition. The range of pathology that drives vasculitis is as broad as the clinical presentation, ranging from general malaise to organ-specific symptoms depending on the blood vessels involved. It is important for GPs to be aware of the disease as it is treatable and can be responsible for significant morbidity and mortality if not managed appropriately. The purpose of this article is to briefly summarise the most common forms of vasculitis, provide guidance on investigating suspected cases, and review the implications of outpatient therapy for the non-specialist.